Design and Development of a Negative Pressure Wound Therapy Device - Citra Ananda Adri Hanifa; Mohammad Rofi’i; Patrisius Kusi Olla (International Journal Science and Technology, 2025)
This study presents the design and development of a Negative Pressure Wound Therapy (NPWT) device aimed at improving the treatment of chronic wounds, particularly diabetic foot ulcers in patients with diabetes mellitus. The primary objective is to create an efficient, user-friendly, and portable wound therapy solution suitable for both clinical and home-based care. The device utilizes negative pressure to enhance blood perfusion, reduce exudate, and lower infection risk, thereby accelerating the healing process. The system is built using a NodeMCU ESP32 microcontroller, a vacuum motor pump, HX710 pressure sensor, solenoid valve, and a Nextion LCD interface. It supports three therapy modes—Continuous, Intermittent, and Dynamic—controlled by a PID algorithm to maintain stable pressure between -25 to -150 mmHg. Testing was conducted at three measurement points: battery voltage, sensor accuracy, and LCD interface functionality. Results indicate that the device performs effectively within expected operational parameters across all modes. The NPWT prototype offers a cost-effective, functional alternative for wound care management and shows promise for further development, including digital integration and broader clinical applications.